Impact of hemodialysis on the state of water compartments in CKD VD patients - Surzhko, L.; Rysev, A.; Molchanova, N. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Understanding of changes in water compartments during hemodialysis (HD) is an important part of ensuring the effectiveness of the procedure and minimizing both intra- and post-dialysis complications. The purpose of our study was to investigate the direction of changes in water sectors in patients with CKD 5D with preserved residual kidney function (RKF) and without RKF. Methods. Prospective observational study enrolled 88 hemodialysis (HD) patients. All patients performed laboratory examinations and measurements of water balance using the BCM monitor before HD, hourly after the start, and 30 minutes after the end of the session. Depending on the presence of residual kidney function, patients were divided into two groups. The first group with RKF included 52 patients, the second - without RKF - 36. Results. Analysis of water balance parameters allowed to conclude that 26 patients (26.13%) were hyperhydrated (OH/ECW above 15%), including 13 (36,11%) in the group without RKF and 10 (19,2%) - in the group with the preserved RKF. There was no statistically significant difference in the groups. When comparing baseline values between groups of patients, it was found that in the group with preserved RKF the albumin level was significantly higher at 8.94% (p<0.05), levels of phosphorus and potassium were lower by 18.27% and 20.24%, respectively. There was no statistically significant difference between other clinical parameters in the groups. Subsequent analysis of the water balance indicators allowed establishing a reliable positive correlation between the level of ultrafiltration (UV) and total body water (TBW). The higher the UV level, the higher the ECW (p < 0.05). Similar results were obtained when analyzing the relationship between extracellular fluid (ECW) and UV (p < 0,001). As a result of the correlation analysis between the level of UV and diuresis, the mean inverse correlation relationship is shown, which shows - the lower the diuresis, the higher the level of ultrafiltration (p < 0,001). During HD the TBW (ΔTBW = 1.5 ± 1.8) and ECW (ΔECW = 1.92 ± 0.85) progressively decrease, the ICW compartment is practically unchanged (ΔICW = -0.17 ± 0.89). In patients with preserved RKF the change in ECW is significantly lower comparatively with the group without RKF (p <0.05). Conclusions. Obtained data indicate that the clinical evaluation of hyperhydration is not always adequate. The obtained results confirm the fact that the presence of RKF provides better phosphorus and potassium levels control in patients with CKD. During HD the removal of fluid occurs directly from the extracellular space, in the group with the RKF to a lesser extent, indicating that the presence of diuresis provides a lower volume of OH, TBW, ECW before HD session, and therefore the level of ultrafiltration appears to be less. Thus the RKF also provides better control of water balance. The results of the dynamics of water sector changes during HD can be used to assess the refilling in the future.